1972
DOI: 10.1111/j.1471-4159.1972.tb01253.x
|View full text |Cite
|
Sign up to set email alerts
|

QUANTITATIVE DETERMINATION OF DNA IN PRESERVED BRAINS AND BRAIN SECTIONS1

Abstract: Abstract— Existing methods for the colorimetric (diphenylamine) determination of DNA content of brain have been modified for preserved cerebral hemispheres. On the average, right and left hemispheres (rat and chicken) contained similar amounts of DNA and one hemisphere could serve as a control for the other. All comparisons have been made with the values obtained for frozen brains (‘controls’). Preservation in 10 % (v/v) buffered formalin for 1 month introduced significant differences for both neonatal and adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1972
1972
1995
1995

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…It has been reported that during malnutrition the organism reduces the catabolism of essential amino acids to urea, and increases activation of amino acids, thus favor ing the incorporation of amino acids into proteins (reviews in 10, 11). Intestinal absorp tion of nutrients (for this reduced amount of food) also improves (14). These improvements may involve inducible enzymes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that during malnutrition the organism reduces the catabolism of essential amino acids to urea, and increases activation of amino acids, thus favor ing the incorporation of amino acids into proteins (reviews in 10, 11). Intestinal absorp tion of nutrients (for this reduced amount of food) also improves (14). These improvements may involve inducible enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…The 'brain', as dissected, was cerebrum without cerebellum and olfactory lobes. DNA was determined by a modification of the diphenylaminc colorimetric method (14); protein was determined by a modification of the Lowry colori metric method (6).…”
Section: Aterials and M E Tho Dsmentioning
confidence: 99%
“…At birth (0 days) or at weaning (30 days in our studies), representative numbers were decap itated; CH were immediately removed, weighed and stored at -1 0 °C for subsequent analysis. DNA was determined by modification of diphenylamine colorimetric methods [17]. Protein contents were determined by the method of Lowry et al [19].…”
Section: Methodsmentioning
confidence: 99%
“…Protein concentration was estimated as in [7] using bovine serum albumin as standard. DNA content of retinas was determined by a modification of the Burton procedure as in [8,9].…”
Section: Methodsmentioning
confidence: 99%